2020
DOI: 10.31258/jkfi.17.2.68-73
|View full text |Cite
|
Sign up to set email alerts
|

SINTESIS DAN KARAKTERISASI NANOPARTIKEL Fe2O3 DARI PASIR ALAM DESA LOGAS KABUPATEN KUANTAN SINGINGI

Abstract: Determination of magnetic and structural properties of natural sand from Logas Village, Kuantan Singingi have been carried out using a magnetic Probe Pasco PS-2162 and X-Ray Diffraction methode. Samples were synthesized using multi step ball milling methode for 90 and 90+30 hours. Results show that the magneticsuceptibility increased with increasing of ball milling time, from 90 hours to 90+30 hours. This magnetic suceptibility within the interval (46-80000) x 10-8 m3/kg which is the interval of Ilminite miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Pasir alam memiliki kandungan mineral oksida besi seperti hematite, magnetite dan maghemite [1][2][3]. Aplikasi sintesis oksida besi berperan besar di nanoteknologi, biomedis, biokompabilitas dan lainnya [4,5]. Sintesis nanopartikel magnetik yang dilakukan oleh peneliti sebelumnya memiliki banyak jenis seperti metode sol gel, metode coprecipitation, metode hydrothermal, metode microwave danmetode ball milling.…”
Section: Pendahuluanunclassified
“…Pasir alam memiliki kandungan mineral oksida besi seperti hematite, magnetite dan maghemite [1][2][3]. Aplikasi sintesis oksida besi berperan besar di nanoteknologi, biomedis, biokompabilitas dan lainnya [4,5]. Sintesis nanopartikel magnetik yang dilakukan oleh peneliti sebelumnya memiliki banyak jenis seperti metode sol gel, metode coprecipitation, metode hydrothermal, metode microwave danmetode ball milling.…”
Section: Pendahuluanunclassified
“…Iron sand is a magnetic material that has the properties of a ferromagnetic material (Gunanto et al, 2018;Karbeka et al, 2021;Yulia and Erwin, 2019). Iron sand has several mineral contents such as hematite (𝛼-Fe 2 O 3 ), maghemite (𝛾-Fe 2 O 3 ), ilmenite (FeTiO 3 ), silica (SiO 2 ), magnetite (Fe 3 O 4 ), alumina (Al 2 O 3 ) and rutile (TiO 2 ) (Nengsi et al, 2016;Sihombing and Amiruddin, 2020;Susilawati et al, 2019). In addition, many unnecessary minerals (gangue) such as K, C, Mg, Na, Si, Al and Ca elements attached to iron ore can reduce the magnetic properties of iron sand.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Tiwow et al found that iron sand from Bontokanang village had a Fe element percentage of 66.7%, while iron sand at Tanjung bayang beach had a Fe element percentage of 79.56%. A greater Fe rate is advantageous for synthesizing Fe3O4 nanoparticles[16],[17]..Figure 1. Research flow diagram Figure 2.…”
mentioning
confidence: 99%